1983
DOI: 10.1210/endo-113-3-1176
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Free Beta Subunit of Human Chorionic Gonadotropin (Hcg) in Cultures of Normal and Malignant Trophoblast Cells, Pregnancy Sera, and Sera of Patients With Choriocarcinoma

Abstract: Immunoaffinity adsorption techniques, utilizing specific antisera for hCG and its subunits bound to Sepharose 4B, have been employed to separate hCG alpha beta dimer and free subunits of hCG. As previously reported by this and a number of other laboratories, trophoblast cells (in vivo and in vitro) produce free alpha subunit in addition to hCG dimer. We have now shown that cultured JAr choriocarcinoma cells also secrete free beta subunit: 37% of the total beta subunit (combined and free) secreted by JAr cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…A variation in the ratio between ß-hCG(I) and hCG(I) activités has been shown to be caused by different amounts of free ß-hCG subunits (Vaitu¬ kaitis 1974; Reuter et al 1980;Cole et al 1983Cole et al , 1984Hay 1985;Norman et al 1985a,b). Like the other glycoproteins hormones, hCG exhibits a considerable polymorphism and in some clinical situations, forms may be secreted with a different degree of cross-reactivity in the ß-hCG or in the hCG assay system, which will also influence the ratio ß-hCG(I)/hCG(I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variation in the ratio between ß-hCG(I) and hCG(I) activités has been shown to be caused by different amounts of free ß-hCG subunits (Vaitu¬ kaitis 1974; Reuter et al 1980;Cole et al 1983Cole et al , 1984Hay 1985;Norman et al 1985a,b). Like the other glycoproteins hormones, hCG exhibits a considerable polymorphism and in some clinical situations, forms may be secreted with a different degree of cross-reactivity in the ß-hCG or in the hCG assay system, which will also influence the ratio ß-hCG(I)/hCG(I).…”
Section: Discussionmentioning
confidence: 99%
“…However, the de¬ gree of cross-reactivity is not known. There is evidence suggesting that native free a-hCG subunits in the placenta and in the circulation are different from those dissociated from purified urinary hCG preparations (Cole et al 1983;Nishimura et al 1983;Posillico et al 1985). There is ample evidence to suggest that the form of hCG produced in early and late pregnancy and in o.ioo Relationship between concentration of hCG(I) and the ratio of ß-hCG(I) to hCG(I) in serum specimens obtained early (E) and late (L) in pregnancy, in women with gestational choriocarcinoma (C), and in men with testicular trophoblastic tumours (T).…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of free hCG␤ correlate not only with the size of the tumor, but also with the malignant potential of the gestational trophoblastic diseases, because it has been shown that more free hCG␤ is secreted by malignant trophoblastic cells than by normal placental trophoblasts. Occasionally, malignant trophoblastic tumors secrete mostly free CG␤ and almost no intact hCG (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In contrast, no significant difference was found when serum hCG was measured during pregnancy with an immunometric assay for hCG or total hCGß [24]. The discrepancy was probably due to the higher production rate of the naturally occuring hCGß in ChCA than during pregnancy, resulting in a higher ratio of hCGß/hCG [6][7][8][9][10][11][12][13]. Nevertheless, immunochemical staining of the tumor for hCGß in the patient with positive total hCGß in serum was found to be negative [4].…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, a technical problem which can readily be solved by validating the assay. As the secretion of free subunit of hCG (naturally occurring hCGß) and its ratio to hCG in patients with ChCA was found to be higher than during pregnancy [6][7][8][9][10][11][12][13], it was postulated that the determination of total hCGß (hCG plus hCGß) in an additive manner would be more advantageous than that of hCG or hCGß by a competitive immunoassay.…”
Section: Introductionmentioning
confidence: 99%